Errors, medicine, and the law / Alan Merry and Alexander McCall Smith. - Merry, Alan; McCall Smith, Alexander, 1948- (Cambridge University Press, 2001)
Untoward injuries are unacceptably common in medical treatment, at times with tragic consequences for patients. The phrases 'an epidemic of error' and 'the medical toll' have been coined to describe this problem of 'iatrogenic harm', which it has been suggested may have contributed to 98,000 deaths per year in the US. Some of these incidents are the result of negligence on the part of doctors, but more usually they are no more than inevitable concomitants of the complexity of modern healthcare. This book is fundamentally about distinguishing the former from the latter. Although medicine is used as the book's primary example, the points made apply equally to aviation, industrial activities, and many other fields of human endeavour. The book advocates a more informed alternative to the blaming culture which has increasingly come to dominate our response to accidents, whether in the medical field or elsewhere.